PENGARUH PEMASARAN BERDASARKAN CONTENT CREATION, CONTENT SHARING, CONNECTING, COMMUNITY BUILDING MELALUI INSTAGRAM TERHADAP BRAND AWARENESS DI UNIVERSITAS INDO GLOBAL MANDIRI PALEMBANG SURVEI PADA FAKULTAS EKONOMI PERIODE MARET – JULI 2020 - Mirja Syafira; Fakhry Zamzam; Luis Marnisah (Integritas Jurnal Manajemen Profesional (IJMPRO), 2021)
Currently, the development of digital marketing, especially on social media Instagram, is increasingly in demand by everyone, of course, this has an impact on the quality of great brand awareness for companies in marketing their goods or services, including universities. In this study, there are five variables used, namely content creation (X1), content sharing (X2), connecting (X3), community building (X4), brand awareness (Y). This type of research in this study uses explanatory research with a quantitative approach. Data collection was obtained through distributing questionnaires online to students of the Faculty of Economics who are still active in the even semester in 2019. The sample used in this study amounted to 275 respondents. The sampling technique used was purposive sampling with descriptive analysis and multiple linear regression. The result of this research is content creation (X1), which has a positive and significant effect on brand awareness (Y) of social media Instagram, Indo Global Mandiri University. Content sharing (X2) has not had a positive and significant impact on brand awareness (Y) of the social media Instagram at Indo Global Mandiri University. Connection (X3) has not had a positive and significant influence on brand awareness (Y) of the social media Instagram at Indo Global Mandiri University. Community building (X4) has not had a positive and significant impact on brand awareness (Y) of the social media Instagram at Indo Global Mandiri University. However, all variables (X) have a joint influence on brand awareness (Y) of social media Instagram, Indo Global Mandiri University.